La construcción religiosa de la Hélade imperial: El Panhelenion - Gordillo Hervas, Rocio (Premio Tesi di Dottorato, 2012)
The coming of Greece under Roman rule marks the beginning of a series of political, administrative and most of all religious transformations, with particular regard to the diffusion across the Greek world of the Imperial Cult as an instrument of territorial cohesion. The present study focuses on a specific period, the second century AD, during which the Panhellenion, a league that incorporates those populations which share a connection with the traditional Greek world, is founded under the auspices of the emperor Hadrian. The analysis of the construction of a new Greek identity has its focus on the Panhellenion, the creation of which stems from the exchange between the imperial power and the city-elites, and on the means employed by the various cities for the renegotiation of their own indentity.